Better a Shrew than a Sheep Women, Drama, and the Culture of Jest in Early Modern England - Brown, Pamela Allen (Cornell University Press, 2018)
In a study that explodes the assumption that early modern comic culture was created by men for men, Pamela Allen Brown shows that jest books, plays, and ballads represented women as laugh-getters and sought out the laughter of ordinary women. Disputing the claim that non-elite women had little access to popular culture because of their low literacy and social marginality, Brown demonstrates that women often bested all comers in the arenas of jesting, gaining a few heady moments of agency. Juxtaposing the literature of jest against court records, sermons, and conduct books, Brown employs a witty, entertaining style to propose that non-elite women used jests to test the limits of their subjection. She also shows how women's mocking laughter could function as a means of social control in closely watched neighborhoods. While official culture beatified the sheep-like wife and disciplined the scold, jesting culture often applauded the satiric shrew, whether her target was priest, cuckold, or rapist. Brown argues that listening for women's laughter can shed light on both the dramas of the street and those of the stage: plays from The Massacre of the Innocents to The Merry Wives of Windsor to The Woman's Prize taught audiences the importance of gossips' alliances as protection against slanderers, lechers, tyrants, and wife-beaters. Other jests, ballads, jigs, and plays show women reveling in tales of female roguery or scoffing at the perverse patience of Griselda. As Brown points out, some women found Griselda types annoying and even foolish: better be a shrew than a sheep